PENYELESAIAN PERSAMAAN NON LINEAR MENGGUNAKAN METODE ITERASI TIGA LANGKAH - Huang, Nafisha Hurinia; Rizal, Yusmet (Journal of Mathematics UNP, 2025)
The Three-Step Iterative Method is a multistep approach designed to determine the roots of complex non-linear equations. Developed using Taylor Series, Quadratic Equations, and Hermite Interpolation, this method provides an alternative for solving complicated equations numerically and analytically. This study aims to examine the formulation of the method, design an algorithm in a flowchart, and analyze its convergence order. The research adopts a literature review methodology by conducting an in-depth analysis of relevant references. The algorithm's implementation is tested through computer programming to evaluate its numerical effectiveness. The results demonstrate that the method achieves high-order convergence, enabling faster solutions with minimal error. In conclusion, the Three-Step Iterative Method is an efficient and accurate solution for resolving complex non-linear equations.